Sexual violence: a descriptive study of victims attended at a center in Brazil. - Martelli, Ellen; Damaso, Enio; Tedesco, Jaqueline; Nadai, Mariane (Brazilian Journal of Implantology and Health Sciences, 2023)
Objective: To examine the socio-demographic profile and assault characteristics of female victims of sexual violence in a Brazilian city. Method: This quantitative retrospective study evaluated female victims of sexual violence between September 2018 and March 2020. Results: Most women were young, single, with less than 11 years of formal education. All perpetrators were male, adults (62.3%), and 77.5% were known to the victims. Multiple offender cases (53.0%) and domestic (56.1%) were the most common incidents. Rape was the primary form of violence (74.5%), with physical force being the most frequently used method of aggression (71.4%). Additionally, 74.5% of victims formalized a police report. Conclusion: This study sheds light on important characteristics of female victims of sexual violence. Given the significant impact of sexual violence on women's health, these findings can inform the development of local health policies to mitigate the consequences of sexual violence.